2016
DOI: 10.1080/17453674.2016.1228411
|View full text |Cite
|
Sign up to set email alerts
|

Over-optimistic patient expectations of recovery and leisure activities after arthroscopic meniscus surgery

Abstract: Background and purpose — Patients’ expectations of outcomes following arthroscopic meniscus surgery are largely unknown. We investigated patients’ expectations concerning recovery and participation in leisure-time activities after arthroscopic meniscus surgery and the postoperative fulfillment of these.Patients and methods — The study sample consisted of 491 consecutively recruited patients (mean age 50 (SD 13) years, 55% men) who were assigned for arthroscopy on suspicion of meniscus injury and later verified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 42 publications
1
30
0
3
Order By: Relevance
“…30 A second study of arthroscopic meniscus surgery revealed that patients' preoperative expectations were overly optimistic for recovery time and return to leisure activities. 31 These studies provide support for our finding that patients who have previously undergone ipsilateral knee surgery have lower expectations, possibly because they have greater knowledge of knee surgery and experience with the postoperative course of recovery. Similar to our finding that better scores for PROMIS Physical Function, IKDC, pre-injury Tegner Activity Scale, and lower extremity MARX ARS correlate with greater overall expectations or expectations for individual MODEMS domains, Pihl et al determined that patients with better baseline knee function who underwent arthroscopic meniscus surgery had higher expectations.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…30 A second study of arthroscopic meniscus surgery revealed that patients' preoperative expectations were overly optimistic for recovery time and return to leisure activities. 31 These studies provide support for our finding that patients who have previously undergone ipsilateral knee surgery have lower expectations, possibly because they have greater knowledge of knee surgery and experience with the postoperative course of recovery. Similar to our finding that better scores for PROMIS Physical Function, IKDC, pre-injury Tegner Activity Scale, and lower extremity MARX ARS correlate with greater overall expectations or expectations for individual MODEMS domains, Pihl et al determined that patients with better baseline knee function who underwent arthroscopic meniscus surgery had higher expectations.…”
Section: Discussionsupporting
confidence: 62%
“…Similar to our finding that better scores for PROMIS Physical Function, IKDC, pre-injury Tegner Activity Scale, and lower extremity MARX ARS correlate with greater overall expectations or expectations for individual MODEMS domains, Pihl et al determined that patients with better baseline knee function who underwent arthroscopic meniscus surgery had higher expectations. 31 Another study regarding public perception of anterior cruciate ligament surgery found that participants, who likely had high levels of physical function, were highly concerned about returning to activity. 32 Additionally, studies in patients undergoing total knee arthroplasty have shown that the majority of patients expected improvement in daily activities and participation in sports; however, these studies did not consider preoperative knee and physical function.…”
Section: Discussionmentioning
confidence: 99%
“…This is also the first study to evaluating patients’ expectations and satisfaction of MAT, taking into account prior procedures to the knee. For general meniscal surgery, it has been reported that patients expect fast recovery and a high level of participation in leisure activities [ 15 ]. However, in this study, less than half of the patients were able to participate at the same competition level as they expected preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…4 Such surgery results in transient increase in pain and the necessity for restriction in activities for a period of 2–12 weeks. 5 6 Current guidelines recommend against arthroscopic lavage and/or debridement for patients with symptomatic knee osteoarthritis, but do not make specific recommendations for or against partial meniscectomy in those with degenerative meniscal tears (with or without other concomitant degenerative changes). 7 8 Further, many orthopaedic surgeons suggest that patients with mechanical symptoms and meniscal tears—typically locking or catching of the knee—may benefit from arthroscopic partial meniscectomy.…”
Section: Introductionmentioning
confidence: 99%